MORAL THOUGHT OF NGUYEN AN NINH - Long, Cao Xuan; Diep, Nguyen (International Journal of Psychosocial Rehabilitation, 2020)
Nguyen An Ninh (1900 - 1943) was a typical Vietnamese thinker in the late 19th and early 20th century. Throughout his life, he left many unique and valuable perspectives, among which is the thought on morality. The contents of moral thought expressed by him were rather diverse and relatively systematic in many aspects, such as: definition of morality, the role of morality, contents of moral standards, methods of moral cultivation, etc. However, the core of his moral thought is liberating the nation, liberating the country, liberating people and leading people to a better life. That's also the requirement of the historical-social practice at that time. If certain limitations of this thought are excused, it can become useful history lessons for the construction and development of each country today.